PERAN POJOK BACA DALAM MENINGKATKAN MINAT BACA ANAK DI DINAS PERPUSTAKAAN DAN KEARSIPAN KABUPATEN PAKPAK BHARAT - Sarida Sinulingga; Hasan Sazali; Yusniah Yusniah (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research aims to find out the role of reading corners in improving children's reading at the Pakpak Bharat Regency Library and Archives Service. The role of reading corners in increasing children's interest in reading, supporting factors and inhibiting factors in increasing children's interest in reading in Pakpak Bharat Regency. This type of research uses qualitative research with a descriptive approach. In this research, data collection was carried out using observation, interviews and documentation methods. Data analysis carried out in this research used data collection techniques, data reduction, data presentation and drawing conclusions. The results of this research show that the reading corner has played an active role in increasing interest in reading because the children there take the time to visit the reading corner. The supporting factor for the role of the reading corner is the existence of facilities in the reading corner and the inhibiting factors in increasing interest in reading in the reading corner include some visitors to the reading corner not being able to look after their books after reading, so some books are damaged.